Altered gut microbiota of obesity subjects promotes colorectal carcinogenesis in mice - Kang, Xing (2023)
Background: Obesity is a risk factor for colorectal cancer (CRC). The role of gut microbiota in mediating the cancer-promoting effect of obesity is unknown. Methods: Azoxymethane (AOM)-treated, ApcMin/+ and germ-free mice were gavaged with feces from obese individuals and control subjects respectively. The colonic tumor load and number were recorded at the endpoint in two carcinogenic models. The gut microbiota composition and colonic transcriptome were assessed by metagenomic sequencing and RNA sequencing, respectively. The anticancer effects of bacteria depleted in fecal samples of obese individuals were validated. Findings: Conventional AOM-treated and ApcMin/+ mice receiving feces from obese individuals showed significantly increased colon tumor formation compared with those receiving feces from control subjects. AOM-treated mice receiving feces from obese individuals showed impaired intestinal barrier function and significant upregulation of pro-inflammatory cytokines and activation of oncogenic Wnt signaling pathway. Consistently, transferring feces from obese individuals to germ-free mice led to increased colonic cell proliferation, intestinal barrier function impairment, and induction of oncogenic and proinflammatory gene expression. Moreover, germ-free mice transplanted with feces from obese human donors had increased abundance of potential pathobiont Alistipes finegoldii, and reduced abundance of commensals Bacteroides vulgatus and Akkermansia muciniphila compared with those receiving feces from human donors with normal body mass index (BMI). Validation experiments showed that B. vulgatus and A. muciniphila demonstrated anti-proliferative effects in CRC, while A. finegoldii promoted CRC tumor growth. Interpretation: Our results supported the role of obesity-associated microbiota in colorectal carcinogenesis and identified putative bacterial candidates that may mediate its mechanisms. Microbiota modulation in obese individuals may provide new approaches to prevent or treat obesity-related cancers including CRC.